LRRK2-Related Parkinson’s Disease Due to Altered Endolysosomal Biology With Variable Lewy Body Pathology: A Hypothesis - Rivero-Ríos, Pilar; Romo-Lozano, María; Fasiczka, Rachel; Naaldijk, Yahaira; Hilfiker, Sabine (Frontiers in Neuroscience, 2020)
Mutations in the gene encoding for leucine-rich repeat kinase 2 (LRRK2) are associated with both familial and sporadic Parkinson´s disease (PD). LRRK2 encodes a large protein comprised of a GTPase and a kinase domain. All pathogenic variants converge on enhancing LRRK2 kinase substrate phosphorylation, and distinct LRRK2 kinase inhibitors are currently in various stages of clinical trials. Although the precise pathophysiological functions of LRRK2 remain largely unknown, PD-associated mutants have been shown to alter various intracellular vesicular trafficking pathways, especially those related to endolysosomal protein degradation events. In addition, biochemical studies have identified a subset of Rab proteins, small GTPases required for all vesicular trafficking steps, as substrate proteins for the LRRK2 kinase activity in vitro and in vivo. Therefore, it is crucial to evaluate the impact of such phosphorylation on neurodegenerative mechanisms underlying LRRK2-related PD, especially with respect to deregulated Rab-mediated endolysosomal membrane trafficking and protein degradation events. Surprisingly, a significant proportion of PD patients due to LRRK2 mutations display neuronal cell loss in the substantia nigra pars compacta in the absence of any apparent α-synuclein-containing Lewy body neuropathology. These findings suggest that endolysosomal alterations mediated by pathogenic LRRK2 per se are not sufficient to cause α-synuclein aggregation. Here, we will review current knowledge about the link between pathogenic LRRK2, Rab protein phosphorylation and endolysosomal trafficking alterations, and we will propose a testable working model whereby LRRK2-related PD may present with variable LB pathology.